Effect of Corporate Social Responsibility on Corporate Profitability - Puput Priyamanda; Fitri Dwi Jayanti (Jibaku: Jurnal Ilmiah Bisnis, Manajemen dan Akuntansi, 2021)
This study aims to analyze the effect of Corporatae Social Responsibility disclosure on Profitability on manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2019. Corporatae Social Responsibility is measured using CSR index based on 4th generation Global Reporting Initiave (G4). Profitability is measured by Return On Asset, Return On Equity, Earning Per Share and Net Profit Margin. The population used in this study is all manufacturing companies listed on the Indonesia Stock Exchange in the period 2018-2019. The research samples used were manufacturing companies that revealed Corporatae Social Responsibility reports in 2018 and 2019 using purposive sampling methods. There were 78 companies in 2018 and 81 companies in 2019 that met the criteria as research samples. The analysis tool used to test hypotheses is Partial Least Square. The results showed that Corporatae Social Responsibility positively and significantly affects profitability by using Net Profit Margin proxy, while using Return On Asset, Return On Equity and Earning Per Share proxy, Corporatae Social Responsibility has no effect on profitability.